Applied longitudinal data analysis modeling change and event occurrence - Singer, Judith D.; Willett, John B. (New York ; Oxford : Oxford University Press, 2003)
The investigation of change has fascinated researchers for generations, and to do it well, they must have longitudinal data. This text instructs readers in the methodologies at their disposal, including both individual growth modelling and survival analysis.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Longitudinal method; Social sciences -- Research